Does Rohu (Labeo rohita) (F. Hamilton, 1822) have different forms of Immunoglobulins? - Suresh Babu, P. P.; Shankar, K. M.; Honnananda, B. R.; Abhiman, P. B. (Fishery Technology, 2017)
Characterisation of immunoglobulin (Ig) is anessential prerequisite for development of anti- fishIg antibody. There are number of reports describingthe characteristics of rohu Ig which state theexistence of different forms of antibodies in rohu.The present review is an attempt to compile thesereports for analyzing the probable reason for theexistence of such forms and the possible futureresearch requirements for confirming the same.